An Investigation on Liquid Chromatographic Technique for Simultaneous Measurement of Alprazolam and Mebeverine in Pharmaceutical Dose Form: Development of an Isocratic RP-LC Method for the Analysis of Alprazolam and Mebeverine in Pharmaceutical Dose Form (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A delicate, quick, exact and reproducible Isocratic, RP-LC strategy was created for assurance of Alprazolam and Mebeverine in pharmaceutical measurement frame. A Sunfire C18, 5 pm segment with portable stage containing methanol cradle (0.02M KH2P04) (7030). The stream rate was 1.0 mlmin and effluents were observed at 225 nm with help of PDA identifier. The maintenance time was 6.04 min. for ALP and 3.53 min. for MEB. The linearity was in the scope of 0.05-40 ggml for ALP and 0.2-40 pigml for MEB. The proposed strategy was approved regarding linearity, exactness, accuracy, specificity and strength. Because of straightforwardness, rate and exactness of technique, trust that the strategy will be helpful for routine quality control examination.